(untitled) (PHARMACON, 2022)
ABSTRACT Aaptos aaptos Sponge is one of the marine biota that is very prospective as a source of natural compounds such as peptides, terpenoids, steroids, acetogenins, alkaloids, cyclic halides and nitrogen compounds. This study aims to determine whet her there is antibacterial activity of the extract and fraction of Sponge Aaptos aaptos from Manado Bay waters against microbes Staphylococcus aureus and Escherichia Coli. Aaptos aaptos Sponge was extracted with 95% ethanol as solvent, fractionation using partition method with n-hexane, choloform and methanol as solvent and antibacterial testing usingagar diffusion method Kirby Baeur. The best antibacterial activity was found in the methanol fraction with an inhibitory power of 18.12 mm against Escherichia Coli bacteria, and an inhibitory power of 14.71 mm on Staphylococcus aureus. The results of this study indicate that the methanol fraction of the Aaptos aaptos Sponge has the ability to inhibit Staphylococcus aureus and Escherichia coli bacteria which can be categorized as strong. Keywords :Aaptos aaptos Sponge, Antibacterial, Staphylococcus aureus, Escherichia ABSTRAK Spons Aaptos aaptos merupakan salah satu biota laut yang sangat prospektif sebagai sumber senyawa bahan-bahan alami antara lain peptida, terpenoid, steroid, asetogenin, alkaloid, halida siklik dan senyawa nitrogen. Penelitian ini bertujuan untuk untuk mengetahui apakah terdapat aktivitas antibakteri dari ekstrak dan fraksi Spons Aaptos aaptos dari perairan Teluk Manado terhadap mikroba Staphylococcus aureus dan Escherichia coli. Spons Aaptos aaptos diekstraksi dengan pelarut eanol 95%, fraksinasi menggunakan metode partisi dengan pelarut n-heksan, kloroform dan metanol dan pengujian antibakteri menggunakan metode difusi agar Kirby Bauer. Aktivitas antibakteri paling baik terdapat pada fraksi metanol dengan daya hambat sebesar 18,12 mm menghambat bakteri Escherichia coli, dan daya hambat sebesar 14,71 mm pada Staphylococcus aureus. Hasil penelitian ini menunjukan bahwa fraksi metanol Spons Aaptos aaptos memiliki kemampuan menghambat bakteri Staphylococcus aureus dan Escherichia coli yang dapat dikategorikan kuat. Kata Kunci: Spons Aaptos aaptos, Antibakteri, Staphylococcus aureus, Escherichia coli